Investing in African agriculture to halve poverty by 2015 - Fan, Shenggen; Johnson, Michael E.; Saurkar, Anuja; Makombe, Tsitsi (International Food Policy Research Institute, 2008)
This paper proposes a simple methodology to estimate the agricultural spending that will be required to achieve the Millennium Development Goal of halving poverty by 2015 (MDG1) in 30 sub-Saharan African countries. This method uses growth-poverty and growth-expenditure elasticities to estimate the financial resources required to meet the MDG1, considering both the direct and indirect impacts of agricultural spending on poverty reduction. The paper attempts to address a key knowledge gap by improving estimation of MDG costs at both the regional and country levels.